Labor Turnover and Labor Legislation in Brazil - Gustavo Gonzaga (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2003)
One of the main characteristics of the Brazilian labor market is its impressively high job and worker turnover rates. Although labor legislation in Brazil is very restrictive, dismissal costs are not high when compared with other Latin American countries. Moreover, many authors argue that the design of some job security programs creates perverse incentives that generate labor turnover. The objective of this paper is twofold. First, we describe Brazilian labor legislation, with emphasis on job security provisions and their incentives on workers reallocation. Then, after reviewing the most recent evidence on labor turnover in Brazil, we investigate the effects of changes in job termination costs implemented in the 1988 Constitution and in a Labor Law of September 2001 on employment duration. Both legislation changes increased firing costs and should have, therefore, reduced turnover for formal workers affected by them. A simple differences-in-differences methodology is applied to monthly individual data from Pesquisa Mensal de Emprego (PME, IBGE), which has information on previous employment spells for those currently unemployed. The results establish that both changes reduced turnover for formal workers affected by the legislation. A significant increase in average employment duration of affected workers relative to not affected workers was observed after both legislation changes. We also provided evidence that the 1988 Constitutional change reduced the probability of fake layoffs, although there are still a high number of such agreements being made between workers and their employers.
Keywords: J63; J64; J65; J68; 330; Labor Turnover; Employment Duration; Job Security Provisions in Brazil; Arbeitsmobilität; Arbeitsrecht; Kündigungsschutz; Brasilien